(3GddBdi GdeVjI aj CNHGQ CFeI GdRjOjI hGdYJQI GdPcjIs - (3CMeO Hf eMeO Hf UdGM GdTQais; (3GdRMjas ((3UdGM Hf CMeO GdegOi Hf eMeO Hf Ydi s)
(3ChdgG (B:s
(3abO PcQfG ai GdLRCjf GdChdjf ef MhGOK GdReGf hJbdHg HUfha GdEeJMGf hdeG GfJgi TQM eG PcQg GdTjN EHQGgje Hf eMeO ai GdHSGeI PcQ eG SfM ef GdMhGOK Edi ReGfg hReGf eUfa GdTQM eMeO Hf Ydi s
(3BNQgG (B:s
(3GfJgi eG CQOJ fbdg ef cJGH Gdabjg HJGQjN (B1053(3g` Je s
(3GNJUGQ dTQM GdRMja Ydi GdbUjOI GdHSGeI ai SjQ CFeI GdRjOjIs
(3hbO CVGa EdjgG GdMhGOK GdeJCNQI HYO (B913(3g Edi SfI (B1053(3g`s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs